2010
DOI: 10.1097/hjh.0b013e32833e1187
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation index and central aortic blood pressure in patients with abdominal aortic aneurysms

Abstract: Augmentation index did not differ in patients with fast and slow-progressing AAA. However, fast progressors had higher central aortic blood pressures suggesting that elevated aortic blood pressure is a risk factor for faster AAA progression, but this needs to be proven in controlled interventional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…However, these data do not completely rule out a potential link between blood pressure and AAA in general or in different animal models. Recent studies have shown that, in humans with AAA, elevated aortic blood pressure is a considerable risk factor for AAA progression [6]. Therefore, it remains a clinically relevant question to examine the role blood pressure plays in AAA formation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, these data do not completely rule out a potential link between blood pressure and AAA in general or in different animal models. Recent studies have shown that, in humans with AAA, elevated aortic blood pressure is a considerable risk factor for AAA progression [6]. Therefore, it remains a clinically relevant question to examine the role blood pressure plays in AAA formation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…The 17 studies included a total of 4873 patients. The definitions of AAA and PAD, cohort size (range 30–1658) and population characteristics varied between studies ( Table ; an expanded version is available as Table S2 , supporting information). Only one study was a specifically designed case–control study with the explicit aim of assessing the association between PAD and AAA growth.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 identified studies, four were rated as high quality, nine as average quality and four as low quality ( Table S4 , supporting information). Four studies failed to report the exact AAA case definition and nine failed to report the exact PAD case definition used. Only five 10,21–23,27 studies adjusted their analyses to account for differences in initial AAA diameter, smoking and diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for other case-control studies, the matching of the patients with controls is critical and its inherent limitations might explain the diversity of results. As far as indices of wave refl ection are concerned, augmentation index seems to be higher in aortic aneurysm (thoracic or abdominal) patients compared to controls [ 39 , 41 ]; however, it does not seem to be able to discriminate between patients with fast and slow progression of aortic aneurysm in their early phase [ 42 ] but rather in their late phase [ 43 ]. On the contrary, central BP shows a steady incremental value over peripheral BP in prediction of fast progression, dissection, and rupture of aortic aneurysm [ 43 ].…”
Section: Aortic Aneurysmsmentioning
confidence: 99%